PENGEMBANGAN BAHAN AJAR DALAM BENTUK MEDIA KOMIK MATERI SISTEM EKSKRESI PADA SISWA KELAS VIII SMP NEGERI 3 TOMPASOBARU - Trifena G Sjawal; Jovialine A Rungkat; Widya A Tumewu (SOSCIED, 2023)
This study aims to develop teaching materials in the form of comic media for excretory system material, grade VIII junior high school in science subjects. This development research uses the ADDIE model which consists of the stages of analyze, design, development, implementation, and evaluation. From the results of the study in the form of a percentage of product validity from the validation sheet obtained from the test results by material experts, media experts, teachers and limited trials on students at SMP Negeri 3 Tompasobaru. The validation results from material experts show that the level of validity of the product that has been developed with a percentage of 96% which is in the very feasible category, media experts with a percentage of 95.29% which is in the very feasible category, from teachers with a percentage of 92% which is in the very feasible category and the results of a limited trial with a percentage of 96.66% in the very good category. So it can be concluded that the teaching materials in the form of comic media on excretory system material for class VIII junior high school students are very valid and feasible to use